2018
DOI: 10.1039/c8gc00381e
|View full text |Cite
|
Sign up to set email alerts
|

H2O2-mediated metal-free protocol towards unsymmetrical thiosulfonates from sulfonyl hydrazides and disulfides in PEG-400

Abstract: A series of unsymmetrical thiosulfonates were successfully prepared from sulfonyl hydrazides and disulfides with the assistance of H2O2 (7.0 equiv.) in PEG-400 at 100 °C, releasing N2 and H2O as byproducts. EPR analysis proved the protocol proceeded through a free radical pathway and a plausible mechanism was proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 61 publications
0
23
0
Order By: Relevance
“…In the presence of sulfonyl hydrazides and oxidative conditions, thiophenols, thioalcohols, disulfides, or sulfonyl hydrazide itself would convert into thiosulfonates (Eq. 42‐1).…”
Section: Formation and Application Of Thiosulfonatesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the presence of sulfonyl hydrazides and oxidative conditions, thiophenols, thioalcohols, disulfides, or sulfonyl hydrazide itself would convert into thiosulfonates (Eq. 42‐1).…”
Section: Formation and Application Of Thiosulfonatesmentioning
confidence: 99%
“…This is a radical mechanism. For example, Dong and co‐workers utilized 0.5 equivalent of R 1 SSR 1 to act as 1 equivalent of [R 1 S] source in a green protocol (PEG‐400 as solvent, N 2 and H 2 O as byproducts). Wei, Guo, and Liu all reported the thiosulfonate synthesis by only using sulfonyl hydrazides as starting materials (Scheme ).…”
Section: Formation and Application Of Thiosulfonatesmentioning
confidence: 99%
“…We observed that no product formation was occurring in the presence of eosin Y after 12 hours (table 1 entry We were astonished to see that only I2 (Iodine) could bring the desired conversion (Table 1, entry 10), and other catalytic conditions provided the desired product with low reaction yield or no reaction ( Table 1, entries 1-6). Encouraged by these findings, our studies were directed to look at the prospective different molar ratio of iodine and Cs2Co3 (cesium carbonate) with ethanol as a solvent ( Table 1, entry [11][12][13][14], but none of these could match the efficacy of model condition which provided thiosulfonate product 3(a-r) in good yield at room temperature in the presence of blue led light (Table 1, entry 10). To screen the effect of time, the model reaction was undertaken under the prevailing conditions in pressure tube using I2 as a catalyst at varying time duration.…”
Section: Resultsmentioning
confidence: 99%
“…[12]. Recently, the cross-coupling reaction of sulfonyl hydrazides with thiols (or sodium sulfinates with disulfides) has been developed for the preparation of thiosulfonates with the help of transitional metal catalysts [13], Sodium sulfinates [14] and sulfoxides [15] are also important organosulfur compounds. Alternatively, thiosulfonates can be obtained by thiosulfonate exchange reactions of sulfenamides, by the reaction of potassium thiosulfonates with diaryliodonium salts [16].…”
Section: Introductionmentioning
confidence: 99%
“…Besides thiols, disulfides were also proved to be effective substrates for the formation of thiosulfonates [135] . In the presence of H 2 O 2 , the unsymmetrical thiosulfonates were formed with moderate to good yields.…”
Section: Sulfonylation Reaction Using Sodium Sulfinatesmentioning
confidence: 99%